1996
DOI: 10.1111/j.1398-9995.1996.tb04615.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of two structured treatment and teaching programs on asthma

Abstract: The aims of the present study were as follows: 1) to evaluate the medical outcomes of two treatment and educational asthma programs 2) to determine by cost-analysis both cost and economic outcome of the programs 3) to perform a cost-benefit analysis (determining the net cost-benefit) and a cost-effectiveness analysis (determining the cost per unit of effect and the incremental cost-effectiveness ratio) from the perspective of health program policy makers (HPP; indirect costs, i.e., loss of productivity, exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…A number of previous studies, including a controlled trial conducted by the present authors9 group [15], have demonstrated that training in asthma selfmanagement that involves self-monitoring by either PEFR or symptoms appears to improve health outcomes for adults with asthma, at least in the short term [2][3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27]. Training programmes which enable people to adjust their medication using a written action plan appear to be more effective than other forms of asthma self-management [25].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies, including a controlled trial conducted by the present authors9 group [15], have demonstrated that training in asthma selfmanagement that involves self-monitoring by either PEFR or symptoms appears to improve health outcomes for adults with asthma, at least in the short term [2][3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27]. Training programmes which enable people to adjust their medication using a written action plan appear to be more effective than other forms of asthma self-management [25].…”
Section: Discussionmentioning
confidence: 99%
“…3). This observation seems common when considering cost evaluations for asthma [13,14,32,33]. For example, within the USA, 10% of asthmatic patients accounted for 44% of the total medical costs of treating the condition [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous costeffectiveness assessments after asthma education are rare and of limited applicability to clinical practice. KAUPPINEN et al [13] reported an improvement in the forced expiratory volume in one second (FEV1) at higher costs without performing a sensitivity analysis and NERI et al [14] described the cost of one day of admission being prevented.…”
mentioning
confidence: 99%
“…Es decir, debe promover la adquisición de habilidades que permitan a los niños y/o a sus padres prevenir o manejar adecuadamente las crisis asmáticas 6,7 . Sin embargo, para atribuir los cambios en el conocimiento acerca del asma a la intervención educativa en lugar de atribuirlos a un error en la medición, es necesario contar con un instrumento de medición válido, fiable y sensible al cambio 8 .…”
unclassified